Pre Modern Interfaith Dialogue Muslim Engagements With Buddhist Thought Before Colonialism - Amara Mir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper explores the nature and dynamics of pre-modern interfaith dialogue between Muslims and Buddhists, focusing on the intellectual and cultural exchanges that occurred prior to the advent of colonialism. This research looks at how early Muslim scholars, travelers, and historians engaged with Buddhist thought not merely through polemical critique, but often with genuine curiosity and attempts at understanding. Through travel accounts, translations, and theological discussions particularly in regions such as India, Central Asia, and parts of the Islamic Caliphate where the two communities coexisted muslim thinkers encountered and reflected on Buddhist teachings, practices, and institutions. These engagements were shaped by the socio-political and religious contexts of their time, yet they reveal moments of intellectual openness and cross-cultural learning. This research paper challenges by examining these early interactions the perception that meaningful Muslim-Buddhist dialogue is a modern phenomenon. It argues that interfaith engagement has deeper historical roots, and that pre-modern encounters offer valuable insights into how religious communities negotiated difference, sought common ground, and contributed to a shared human heritage before the disruptions of colonialism and modernity reframed their relationships.